Formulation and Characterization of Secretome Hydrogel Based on Sodium Alginate as Anti-Aging - Alquraisy, Ayatulloh; Wathoni, Nasrul; Wilar, Gofarana; Suhandi, Cecep (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Hydrogel can be developed as a secretome delivery strategy for controlled release, thereby extending the residence time of the secretome and providing safer and more effective therapeutic effects. Secretome has great potential to prevent skin aging. The enzymes contained in the secretome have antioxidant activity. This study aimed to determine the characterization and anti-aging activity of sodium alginate-based secretome hydrogel preparations. In this research, hydrogel secretome characterization tests were carried out in the form of organoleptics, pH, viscosity, spreadability, HRTEM and also anti-aging activity testing using the DPPH scavenging assay method. The organoleptic test showed that all formulas were pale yellow in color, soft and homogeneous in consistency. pH, viscosity and spreadability tests showed that all formulas entered the standard range for topical preparations. Taking images of the hydrogel surface using HRTEM shows that the secretome has been successfully dispersed into the hydrogel. Anti-aging activity testing carried out has also proven an increase in the percentage of inhibition and IC50 value in the formula along with increasing the secretome dose.